Beyond the Binary: Queer Media Engagement's Role in Shaping LGB Youth Identity Formation - Espina, Rochelle Margaux I.; Cai, Kimberly B.; Ke, Sam Wei Quan P.; Marco, Daiseree A.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2025)
This study examined the associations between queer media engagement, demographic factors, and social identity formation among Filipino lesbian, gay, and bisexual (LGB) undergraduate students (N = 52, aged 18-24) using correlational analysis. Spearman's rank correlation coefficient (ρ) revealed a significant positive association between monthly family income and queer media engagement (ρ= 0.28, p < .05), suggesting socioeconomic factors influence access to identity-affirming media resources. Weekly hours of media consumption demonstrated the strongest relationship with overall engagement level (ρ = 0.43, p < .01), validating the multidimensional nature of queer media engagement. Contrary to prevalent assumptions, findings showed a non-significant negative correlation between queer media engagement and identity formation (ρ = -0.16, p >.05), suggesting a more complex relationship than previously theorized. Analysis of identity formation components revealed stronger development in cognitive aspects (median = 4.0) than behavioral components (median = 2.0-2.5), aligning with established models of LGBTQIA+ identity development where internal affirmation typically precedes external expression. These findings challenge simplistic assumptions about media influence and suggest a nuanced dynamic where socioeconomic factors, developmental stages, and cultural context significantly shape how Filipino LGB youth engage with queer media and integrate these experiences into their identity formation processes. This underscores the importance of addressing potential digital access disparities and developing critical media literacy alongside increased representation.